1/6m+2/3m=650

Simple and best practice solution for 1/6m+2/3m=650 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 1/6m+2/3m=650 equation:



1/6m+2/3m=650
We move all terms to the left:
1/6m+2/3m-(650)=0
Domain of the equation: 6m!=0
m!=0/6
m!=0
m∈R
Domain of the equation: 3m!=0
m!=0/3
m!=0
m∈R
We calculate fractions
3m/18m^2+12m/18m^2-650=0
We multiply all the terms by the denominator
3m+12m-650*18m^2=0
We add all the numbers together, and all the variables
15m-650*18m^2=0
Wy multiply elements
-11700m^2+15m=0
a = -11700; b = 15; c = 0;
Δ = b2-4ac
Δ = 152-4·(-11700)·0
Δ = 225
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$m_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$m_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{225}=15$
$m_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(15)-15}{2*-11700}=\frac{-30}{-23400} =1/780 $
$m_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(15)+15}{2*-11700}=\frac{0}{-23400} =0 $

See similar equations:

| 3z-45=2z-25 | | 20-2n=10-2n | | -3x+10=2x+4 | | (x-0.10x)-70=0.35(70) | | C=38.16+0.50x | | 15/18m=650 | | 5x-22=3x=10 | | 6+63/4x4=27.75 | | (5x-22)=(3x=10) | | 6.47x+58.23=116.46 | | 12x=4+5x^2 | | X/3-2=x/5+2 | | 4(x-1)^(2)=8 | | (5x-22)+(3x=10)=180 | | 8x-4+4X=7x+8 | | 2/3a+10=20 | | 2x+1=2x+31=x+16 | | z/5-1=7 | | 19=7x+4 | | 19=7×+y | | 2.6r+4=20 | | 120(x-20)=0 | | 24x-30=18x+16-3x | | 10(w+3)=90 | | 4(5x+6)-7=2(8+3x)-x | | 56÷b=b=7 | | 4n-1=6n-8-8n+15 | | 8-3a=-22 | | 15-3t=12+-1.6 | | x+19=133/2x+19=133/2x-19=133x+19=133/2 | | C=0.15t=2.15 | | 75+15x=25x+55 |

Equations solver categories